The Influence of Service and E-Service Quality to Repurchase Intention the Mediating Role of Customer Satisfaction. Case Study: Online Transportation by Go-Jek Indonesia - Santoso, Agus; Aprianingsih, Atik (Journal of Business and Management, 2017)
Abstract. Repurchase intention in the business world becomes critical to increasing the company's revenue. One of them is by improving the service quality which impacts on improving customer satisfaction and repurchase intention by customers. This study examined the relationship between the influence of the service quality and e-services quality toward repurchase with customer satisfaction as the intermediate variable. This research especially examines Go-Ride service from Go-Jek Indonesia in Java with the number of respondents of 415 respondents were obtained through a questionnaire. Data analyzed with multilinear regression and path analysis with classical assumption test. This study found that simultaneous or partially perceived service quality, perceived e-service quality, and customer satisfaction has a significant relationship to repurchase intention that determined with sig <0.005. The magnitude of the effect of service quality towards repurchase intention is 0.075, e-service qualityÂ 0.569, customer satisfaction towards repurchase intention is 0.74. Ths study found that customer satisfaction has an important effect to increase the repurchase intention pf Go-Ride by Go-Jek Indonesia.Â Keywords: service quality, e-service quality, customer satisfaction, repurchase intention